Non-native plant invasion after fire in western USA varies by functional type and with climate - Janet S. Prevéy; Catherine S. Jarnevich; Ian S. Pearse; Seth M. Munson; Jens T. Stevens; Kevin J. Barrett; Jonathan D. Coop; Michelle A. Day; David Firmage; Paula J. Fornwalt; Katharine M. Haynes; James D. Johnston; et al. (Biological Invasions, 2024)

Refuge‐yeah or refuge‐nah? Predicting locations of forest resistance and recruitment in a fiery world - Kyle C. Rodman; Kimberley T. Davis; Sean A. Parks; Teresa B. Chapman; Jonathan D. Coop; Jose M. Iniguez; John P. Roccaforte; Andrew J. Sánchez Meador; Judith D. Springer; Camille S. Stevens‐Rumann; Michael T. Stoddard; Amy E. M. Waltz; et al. (Global Change Biology, 2023)
Climate warming, land use change, and altered fire regimes are driving ecological transformations that can have critical effects on Earth's biota. Fire refugia—locations that are burned less frequently or severely than their surroundings—may act as sites of relative stability during this period of rapid change by being resistant to fire and supporting post‐fire recovery in adjacent areas. Because of their value to forest ecosystem persistence, there is an urgent need to anticipate where refugia are most likely to be found and where they align with environmental conditions that support post‐fire tree recruitment. Using biophysical predictors and patterns of burn severity from 1180 recent fire events, we mapped the locations of potential fire refugia across upland conifer forests in the southwestern United States (US) (99,428 km 2 of forest area), a region that is highly vulnerable to fire‐driven transformation. We found that low pre‐fire forest cover, flat slopes or topographic concavities, moderate weather conditions, spring‐season burning, and areas affected by low‐ to moderate‐severity fire within the previous 15 years were most commonly associated with refugia. Based on current (i.e., 2021) conditions, we predicted that 67.6% and 18.1% of conifer forests in our study area would contain refugia under moderate and extreme fire weather, respectively. However, potential refugia were 36.4% (moderate weather) and 31.2% (extreme weather) more common across forests that experienced recent fires, supporting the increased use of prescribed and resource objective fires during moderate weather conditions to promote fire‐resistant landscapes. When overlaid with models of tree recruitment, 23.2% (moderate weather) and 6.4% (extreme weather) of forests were classified as refugia with a high potential to support post‐fire recruitment in the surrounding landscape. These locations may be disproportionately valuable for ecosystem sustainability, providing habitat for fire‐sensitive species and maintaining forest persistence in an increasingly fire‐prone world.

Cover and density of southwestern ponderosa pine understory plants in permanent chart quadrats (2002–2020) - Margaret M. Moore; Jeffrey S. Jenness; Daniel C. Laughlin; Robert T. Strahan; Jonathan D. Bakker; Helen E. Dowling; Judith D. Springer (Ecology, 2022)
This data set consists of 101 permanent 1 m × 1 m (1‐m 2 ) quadrats located within southwestern ponderosa pine ecosystems near Flagstaff, Arizona, USA. Individual plants in these quadrats were identified and mapped annually for 19 years (2002–2020). The original chart quadrats were established between 1912 and 1927 to determine the effects of domestic livestock grazing on herbaceous plants and pine seedlings. Today these data provide opportunities to examine the effects of climate and land‐use change on plant demography, population dynamics, and community processes. We provide the following data and data formats: (1) digitized maps of all plant locations in shapefile and geodatabase format, (2) shapefiles showing annual locations of each individual plant species, (3) annual maps of each quadrat in TIFF and PDF format, (4) annual basal area of each species per quadrat for species mapped as polygons, (5) tabular representation of polygon areas and centroid locations for plant species mapped as polygons, (6) tabular representation of point locations for plant species mapped as points, (7) plot‐scale 20 m × 20 m overstory tree canopy cover, tree basal area, parent material, and elevation, (8) quadrat‐scale information (e.g., quadrat site and number, coordinates in UTM Zone 12 and latitude/longitude, and descriptive comments for each quadrat), (9) plant species list, (10) summary of plant species observed in each quadrat, (11) summary of quadrats mapped by site and year, and (12) data formatted for use in Integral Projection Models (IPM) and plant population analyses. There are no copyright restrictions; please cite this paper and the associated data set when data are used in publications.

Restoring plant species diversity and community composition in a ponderosa pine-bunchgrass ecosystem - Daniel C. Laughlin; Jonathan D. Bakker; Mark L. Daniels; Margaret M. Moore; Cheryl A. Casey; Judith D. Springer (Plant Ecology, 2008)